The Role of the Notary in Preventing and Overcoming Mistakes in Van Omstandigheden Made by Housing Developers in Home Purchase and Sale Credit Agreements through the Developer - Faizal, Akhmad Bagus (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
The implementation of housing credit agreements through housing developers often experiences problems, one of which is fraudulent acts committed by the developer, resulting in losses for both housing buyers and the bank as the loan fund provider. The type of legal research used is non-doctrinal. In this non-doctrinal legal research, law is conceptualized as a manifestation of the symbolic meanings of social actors as seen in the interactions between them. That the real reality of life does not exist in the empirical realm which is also the observational realm, it does not appear in the form of behavior that is patterned and structured objectively (let alone normative) and therefore can be measured to produce quantitative data. The reality of life actually only exists in the realm of meaning which appears in the form of symbols which can only be understood after being interpreted. Such a reality cannot be easily